2019
DOI: 10.3122/jabfm.2019.06.190093
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Palliative Health Care for Homeless and Vulnerably Housed Individuals

Abstract: Background: Thirty-five thousand Canadians are homeless on any given night, and mortality rates are much higher than for the general population. Studies have identified barriers to accessing end-of-life care among the homeless, including logistic barriers and experiences of stigma. This study seeks to explore the experience, goals, fears, and hopes surrounding death in the setting of homelessness or vulnerable housing. Methods: Qualitative phenomenological study involving focus groups and in-depth interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
1
10
0
7
Order By: Relevance
“…Given the care concerns highlighted even among the more stable patients that were ultimately included in the study, our results likely under-represent some of the challenges faced by the most vulnerable (and thus most emotionally dysregulated) patients when they seek care in the ED. This hypothesis is also consistent with literature on healthcare experiences among particularly stigmatized groups [39,40].…”
Section: Strengths and Limitationssupporting
confidence: 91%
“…Given the care concerns highlighted even among the more stable patients that were ultimately included in the study, our results likely under-represent some of the challenges faced by the most vulnerable (and thus most emotionally dysregulated) patients when they seek care in the ED. This hypothesis is also consistent with literature on healthcare experiences among particularly stigmatized groups [39,40].…”
Section: Strengths and Limitationssupporting
confidence: 91%
“…The study samples were predominantly White, middle-aged males, except one that reported a sample of 67.3% female (Baggett et al, 2018), and six publications from the SHADOW study, which included only women, with a majority of the women (72%) identifying as non-White (Riley et al, 2014). The sample sizes ranged from 31 (Purkey & MacKenzie, 2019) to 434,240 participants (Byrne et al, 2019). Most samples were exclusively H/VH participants, except for one study (Baggett et al, 2018) that included the general population who accessed federally funded community health centers.…”
Section: Resultsmentioning
confidence: 99%
“…Although Riley et al (2014) and Purkey and MacKenzie (2019) did not provide separate definitions of homelessness and VH, they included the extrapersonal factors of living environment and housing history in their combined definition for H/VH. Sleeping in public spaces or a homeless shelter (Purkey & MacKenzie, 2019; Riley et al, 2014) and living in substandard conditions unfit for human habitation (Purkey & MacKenzie, 2019) were extrapersonal stressors included in the definitions of H/VH in these studies. Additionally, those at risk of losing their current housing accommodations were an inclusion criterion in one study (Purkey & MacKenzie, 2019), which aligns with the extrapersonal stressor of recent housing history from the definition of VH.…”
Section: Resultsmentioning
confidence: 99%
“…For example, people experiencing homelessness or vulnerable housing are often marginalized and are known to face barriers to accessing appropriate healthcare services ( 9 ). Although changes have been recommended in the complex health systems, so that it should be more equitable, more sensitive and empathic, and more informed about the traumatic situations experienced by homeless people, barriers related to cultural aspects are barely mentioned in those key documents ( 116 118 ). Similar patterns can be seen in the studies of other conditions of vulnerability and adverse circumstances that apparently seem disconnected from their own cultural aspects or they seem irrelevant for health equity ( 119 ).…”
Section: Discussionmentioning
confidence: 99%